Abdominal Surgical Emergencies in the Puerperium: A Descriptive Study - Naseem Saba, Muhammad Hamayun Khan, Neelam Mehsood, Sobia Rashid, Hina Ayub, Momina Ali Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Pseudomonas aeruginosa is a formidable opportunistic pathogen known for its ability to form resilient biofilms, largely regulated by the Multiple Virulence Factor Regulator (MvfR/PqsR) quorum sensing system. Inhibition of MvfR presents a promising strategy to attenuate virulence and overcome antibiotic resistance. Objective: This study aimed to identify potent anti-biofilm flavonoids that inhibit the MvfR protein through computational screening, molecular docking, and dynamics simulations. Methods: A library of 1,200 flavonoids was screened against the crystal structure of MvfR (PDB ID: 4JVC). Initial virtual screening was followed by high-precision molecular docking to evaluate binding affinities and interaction patterns. The stability of the top-ranking ligand-protein complexes was further validated through 100ns Molecular Dynamics (MD) simulations and MM-GBSA binding free energy calculations. Results: Three lead flavonoids Quercetin, Kaempferol, and Luteolin exhibited superior binding affinities compared to the native ligand, with docking scores ranging from -8.5 to -10.2 kcal/mol. Interaction analysis revealed consistent hydrogen bonding with key residues Tyr258 and Ile263. MD simulations confirmed that these compounds remained stably bound within the hydrophobic pocket, maintaining structural integrity throughout the simulation period. MM-GBSA analysis corroborated these findings, indicating favorable energetic profiles for MvfR inhibition. Conclusion: The identified flavonoids show significant potential as MvfR inhibitors, offering a scaffold for developing new anti-biofilm agents. These computational findings provide a robust basis for subsequent in vitro validation to combat P. aeruginosa infections. Keywords: Pseudomonas aeruginosa, MvfR Inhibition, Flavonoids, Molecular Dynamics, Biofilm.